Heat-shrinkable material, heat-shrinkable sleeve and manufacturing method of heat-shrinkable sleeve

By blending bio-based coffee powder with other materials to prepare heat shrink sleeves, the problem of releasing irritating odors and waste of resources in the prior art is solved, and environmentally friendly, degradable and cost-reducing effects are achieved.

CN119463343APending Publication Date: 2025-02-18王彦琛
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411511031.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing heat shrink sleeves will release irritating odors during processing and use, affecting air quality, and have high costs of flame retardants, serious waste of resources, and a long degradation cycle.

Method used

Using bio-based filler coffee powder as raw material, it is blended with ethylene-vinyl acetate copolymer, capacity enhancer, flame retardant and antioxidant, and then extruded and granulated at a preset temperature, and cross-linked by irradiation. and expanding molding to make a heat shrink sleeve.

Benefits of technology

Reduces the irritating odor during manufacturing and use of heat shrink sleeves, reduces costs, has environmentally friendly and degradable properties, and improves the performance and environmental friendliness of wire protection materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463343A_ABST
    Figure CN119463343A_ABST
Patent Text Reader

Abstract

The invention provides a thermal shrinkage material, a thermal shrinkage sleeve and a manufacturing method of the thermal shrinkage sleeve, and the thermal shrinkage material comprises the following components in parts by weight: 40-50 parts of ethylene-vinyl acetate copolymer; 0.5 to 1.5 parts of a compatibilizing aid; 45 to 50 parts of a flame retardant; 0.2 to 0.5 part of an antioxidant; and 1-5 parts of a bio-based filler. According to the heat-shrinkable material, the coffee powder is used as a bio-based filler, and the special fragrance of the coffee powder and the adsorbability of the coffee powder similar to activated carbon are utilized, so that the pungent smell generated in the manufacturing and using processes of the heat-shrinkable sleeve is greatly reduced, the cost is reduced, and the heat-shrinkable sleeve has the characteristics of environment friendliness and degradability; and the performance and environmental friendliness of the wire protection material in the automobile industry are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a heat shrinkable material and a heat shrinkable sleeve and a manufacturing method thereof. Background Art

[0002] In the field of electronic appliances and automobile industry, heat shrink tubing is widely used to protect wire terminals and connector lines. These wires and tubing are usually made of specific plastic raw material formulas, such as low smoke halogen-free or halogen-containing materials. However, there are some problems in the existing technology:

[0003] 1. The existing raw material products have a certain smell. During the gamma ray radiation processing, the gamma ray radiation cracking will produce small molecules, releasing a pungent smell. During the heating and shrinking process, an obvious and unfriendly smell will be produced.

[0004] 2. In cars, especially in the summer when the ambient temperature is high, existing products will release unfriendly odors, affecting the air quality in the passenger compartment.

[0005] 3. The existing flame-retardant heat shrink tubing is expensive due to the addition of flame retardants. As a waste, coffee grounds are currently generally disposed of by landfill or fermentation, which not only wastes resources but also does not meet the current requirements for energy conservation. By adding coffee grounds, material costs can be reduced, weight can be reduced, and waste recycling can be promoted.

[0006] 4. The degradation cycle of radiation-crosslinked polymer materials is long, but adding bio-based coffee grounds can shorten the degradation cycle of radiation-crosslinked polyolefins to a certain extent, which is beneficial to energy conservation and environmental protection.

[0007] Globally, coffee grounds are produced in huge quantities, exceeding 6 million tons per year. At present, the main treatment methods for coffee grounds are incineration and landfill, which not only wastes resources but also pollutes the environment. Therefore, exploring the environmentally friendly industrial application of coffee grounds is of great significance to achieving sustainable development. Summary of the invention

[0008] In view of this, the present invention aims to solve the above-mentioned problems in the prior art and provide a new type of environmentally friendly heat shrinkable tubing material, which uses bio-based fillers such as coffee powder as raw materials, which not only reduces costs but also has environmental protection and degradable properties, thereby improving the performance and environmental friendliness of wire protection materials in the automotive industry.

[0009] In a first aspect, the present invention provides a heat shrinkable material, comprising the following components by weight:

[0010]

[0011] Optionally, the melt index of the ethylene-vinyl acetate copolymer is 1.5-5 grams per minute (g / min), and the vinyl acetate (VA) content is 13%-30%.

[0012] Optionally, the compatibilizing agent is a maleic anhydride graft copolymer, wherein the content of maleic anhydride comonomer is 0.8-1%wt (weight content percentage).

[0013] Optionally, the flame retardant is a compound of aminosilane-modified ore-process magnesium hydroxide and coated red phosphorus, wherein the weight ratio of the aminosilane-modified ore-process magnesium hydroxide to the coated red phosphorus is 5:1.

[0014] Optionally, the antioxidant is one of amines, heterocycles, phenols, thioesters, and phosphites, and the bio-based filler is coffee powder.

[0015] Optionally, the method for preparing the coffee powder includes: grinding coffee beans to extract coffee powder, wherein the particle size of the coffee powder is 2-20 microns (μm), or between 6000 mesh and 600 mesh; and drying the coffee powder.

[0016] In a second aspect, the present invention provides a heat shrinkable sleeve, comprising:

[0017] The heat shrinkable material as described in any one of the above items is used, wherein the heat shrinkable material comprises the following components in parts by weight:

[0018]

[0019] In a third aspect, the present invention also provides a method for manufacturing a heat shrinkable tube, comprising: taking the heat shrinkable material as described in any of the above items; extruding and granulating the heat shrinkable material at a preset temperature to obtain masterbatch particles; extruding the masterbatch particles into shape, and obtaining the heat shrinkable tube through radiation crosslinking and expansion molding.

[0020] The heat shrinkable material provided by the present invention utilizes coffee powder as a bio-based filler, and utilizes the unique aroma of coffee powder and the adsorption property of coffee powder similar to activated carbon, which greatly reduces the irritating taste generated by the heat shrinkable tube during the manufacturing and use process, not only reduces the cost, but also has the characteristics of environmental protection and degradability, thereby improving the performance and environmental friendliness of wire protection materials in the automotive industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in describing the embodiments are briefly introduced below.

[0022] Figure 1 It is a structural schematic diagram of a heat shrinkable sleeve in the prior art;

[0023] Figure 2 A schematic flow chart of a method for preparing coffee powder provided in an embodiment of the present invention;

[0024] Figure 3 A schematic flow chart of a method for manufacturing a heat shrinkable sleeve provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0025] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the specific implementation of the present invention will be described below with reference to the accompanying drawings. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementations can be obtained based on these drawings without creative work.

[0026] In the description of the present invention, the terms "first", "second", etc. are only used to distinguish and describe related objects, and cannot be understood as indicating or implying the relative importance or order between the related objects. The term "comprising: a combination of one or more of a1, a2, ..., an" (n is a positive integer greater than 2) means any one of the described objects, any combination of two objects, any combination of three objects, and any combination of n objects. For example, "combining one or more of a1, a2, a3" includes a1, a2, a3, a1 and a2, a1 and a3, a2 and a3, a1, a2, and a3.

[0027] Please refer to Figure 1 , which is a cross-sectional schematic diagram of a heat shrinkable sleeve in the prior art, such as Figure 1 As shown, the heat shrinkable sleeve 100 is a double-wall heat shrinkable sleeve, including an outer layer (also called outer skin layer) 110 and an inner layer (also called inner rubber layer) 120. The outer layer 110 is made of heat shrinkable material (for example, cross-linked polyolefin, cross-linked polyethylene, etc.), which shrinks when heated (such as Figure 1 The inner layer 120 is made of hot melt adhesive material, which can melt and flow at the temperature at which the outer layer material shrinks, and the flowing hot melt adhesive can fill the gap and conform to the shape of the wrapped object to form a seal. The heat shrinkable sleeve with such a structure has good flame retardant, insulation and other properties, and is soft and elastic, has a low shrinkage temperature, shrinks quickly, and has a wide range of applications.

[0028] At present, heat shrink tubing is usually made of a specific plastic raw material formula. During the production process, the use of gamma rays will produce small molecules and release pungent odors. During use, heating and shrinking will also produce obvious and odorous pungent odors, which not only affects the user experience, but also pollutes the environment to a certain extent.

[0029] Therefore, the embodiment of the present invention provides a new type of environmentally friendly heat shrinkable material, which uses bio-based fillers such as coffee powder as raw materials, which not only reduces costs but also has environmentally friendly and degradable properties, thereby improving the performance and environmental friendliness of wire protection materials in the automotive industry.

[0030] The components and preparation process of this heat shrinkable material are described below.

[0031] The heat shrinkable material comprises the following components by weight:

[0032] 40-50 parts of ethylene-vinyl acetate copolymer;

[0033] 0.5-1.5 parts of compatibilizer;

[0034]

[0035] In the embodiment of the present invention, the melt index of the ethylene-vinyl acetate copolymer is 1.5-5 grams per minute (g / min), and the vinyl acetate (VA) content is 13%-30%.

[0036] As a more preferred technical solution, the ethylene-vinyl acetate copolymer has a melt index of 1.5-2 g / min and a VA content of 14%-28%.

[0037] Ethylene-vinyl acetate copolymer is obtained by introducing vinyl acetate monomer into the ethylene molecular chain, thereby reducing the high crystallinity, improving flexibility, and enhancing the compatibility of the resin with inorganic substances.

[0038] In the embodiment of the present invention, the compatibilizing agent is a maleic anhydride graft copolymer, wherein the content of maleic anhydride comonomer is 0.8-1%wt (weight content percentage).

[0039] As a preferred technical solution, the compatibilizing agent is maleic anhydride grafted onto PE or EVA modified copolymer, and the content of maleic anhydride comonomer is 0.6-0.9%wt.

[0040] In the embodiment of the present invention, the flame retardant is a compound of aminosilane-modified ore-process magnesium hydroxide and coated red phosphorus, and the weight ratio of the aminosilane-modified ore-process magnesium hydroxide to the coated red phosphorus is 5: 1. The flame retardant effect of the compound is better and the cost is lower.

[0041] In an embodiment of the present invention, the antioxidant is a combination of one or more of amines, heterocyclics, phenols, thioesters, and phosphites.

[0042] In an embodiment of the present invention, the bio-based filler is one or more mixtures of ground and extracted coffee powders, and the particle size of the powders is 2-20 μm or between 6000 mesh and 600 mesh.

[0043] In the embodiments of the present invention, see Figure 2 , the preparation method of the coffee powder comprises:

[0044] S110: Grind and extract coffee beans into coffee powder;

[0045] In the embodiment of the present invention, waste coffee grounds can be used as bio-based fillers, which not only greatly saves resources but also greatly reduces pollution to the environment, which is of great significance for achieving sustainable development.

[0046] S120: Drying the coffee powder.

[0047] For example, grind the coffee into a particle size of 2-20 microns (μm), or coffee powder between 6000 mesh and 600 mesh, and then bake it at 150°C for 2 hours to ensure that the moisture content is ≤0.5%.

[0048] This heat shrink material uses coffee powder as a bio-based filler, and takes advantage of the unique aroma of coffee powder and its adsorption properties similar to activated carbon, which greatly reduces the irritating taste produced by the heat shrink tubing during the manufacturing and use process. It not only reduces costs, but also has environmentally friendly and degradable characteristics, improving the performance and environmental friendliness of wire protection materials in the automotive industry.

[0049] See also Figure 3 The method for manufacturing a heat shrinkable tube using a heat shrinkable material provided in an embodiment of the present invention comprises at least the following steps:

[0050] S210: Blending ethylene-vinyl acetate copolymer, a compatibilizing agent, a flame retardant, an antioxidant and a bio-based filler and extruding and granulating at a preset temperature to obtain masterbatch particles.

[0051] For example, the above mixture is extruded through a twin-screw extruder at 125-145° C. to produce masterbatch pellets.

[0052] S220: Extruding the masterbatch particles into shape, and manufacturing a finished heat shrink tubing through processes such as radiation cross-linking and expansion molding.

[0053] For example, the masterbatch particles are extruded through a single screw extruder at 105-115° C., and the finished heat shrinkable sleeve is obtained through processes such as radiation cross-linking and expansion molding.

[0054] In this embodiment, radiation cross-linking using gamma radiation to induce grafting and cross-linking is an effective, fast, clean, user-friendly and controllable technology for polymer materials, which can improve their performance in high-performance applications such as automotive, electrical insulation, ink curing, surface modification under different environments, food packaging, medical, sterilization, health care, etc.

[0055] This type of radiation-crosslinked polymer material has a long degradation period, but by adding bio-based coffee powder, the long degradation period of radiation-crosslinked polyolefins can be shortened to a certain extent, which is beneficial for saving energy and protecting the environment.

[0056] After the above raw material preparation is completed, the prepared raw materials can be used to manufacture heat shrinkable tubes. In the manufacturing process, the α-polyolefin resin graft material and the α-polyolefin resin catalytic masterbatch are mixed in a mass ratio of 80:20 to 95:5 and then fed into the material, and extruded together with the raw materials of the outer layer to obtain a heat shrinkable tube. The extrusion temperature can be set to a preset temperature, and the preset temperature range is, for example, 120 to 180°C.

[0057] Several embodiments are given below to illustrate the composition and preparation of the above heat shrinkable material.

[0058] Example 1

[0059] First, this embodiment provides a low-odor formula: in parts by weight, the raw materials for its preparation include 50.3 parts of ethylene-vinyl acetate copolymer, 1.5 parts of a compatibilizer, 47 parts of a flame retardant, 0.2 parts of an antioxidant, and 1 part of coffee grounds.

[0060] The brand of the ethylene-vinyl acetate copolymer is Mitsui Dupont V421, and the VA content is 28%-29%.

[0061] The compatibilizing agent is a commercially available maleic anhydride grafted EVA polymer, and the grafting rate is preferably 0.8-1%.

[0062] The flame retardant is a compound of aminosilane-modified ore-process magnesium hydroxide and coated red phosphorus in a weight ratio of 5:1;

[0063] The antioxidant is 1010, namely pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0064] The bio-based filler is a mixture of one or more ground and extracted coffee powders (powder particle size is 2-20 μm, or between 6000 mesh and 600 mesh).

[0065] Secondly, this embodiment provides a method for preparing a heat shrinkable sleeve, which at least includes the following steps:

[0066] Blending ethylene-vinyl acetate copolymer, a compatibilizing agent, a flame retardant, an antioxidant and a bio-based filler and extruding the mixture through a twin-screw extruder at 110° C. to produce a masterbatch pellet;

[0067] The masterbatch particles obtained in the above steps are extruded in a single screw extruder at 110°C to obtain a tubular semi-finished product with a wall thickness of 0.5-1.5 mm, and then a tubular finished casing with a wall thickness of 0.35-0.75 mm is obtained through electron accelerator or cobalt 60 irradiation cross-linking, vacuum or pressure expansion molding and other processes.

[0068] Example 2

[0069] First, this embodiment provides a low-odor formula: by weight, its preparation raw materials include 48.3 parts of ethylene-vinyl acetate copolymer, 1.5 parts of a compatibilizer, 45 parts of a flame retardant, and 0.2 parts of an antioxidant. The brand of the ethylene-vinyl acetate copolymer is Mitsui DuPont V421, and the VA content is 28%-29%.

[0070] The compatibilizing agent is a commercially available maleic anhydride grafted EVA polymer, and the grafting rate is preferably 0.8-1%.

[0071] The flame retardant is a compound of aminosilane-modified ore-process magnesium hydroxide and coated red phosphorus in a weight ratio of 5:1;

[0072] The antioxidant is 1010.

[0073] Plastic masking agent or fragrance, the deodorant is a rubber or plastic deodorant sold on the market, 1 part in powder state.

[0074] Secondly, this embodiment provides a method for preparing a heat shrinkable sleeve, which at least includes the following steps:

[0075] The ethylene-vinyl acetate copolymer, the compatibilizer, the flame retardant and the antioxidant are blended and extruded by a twin-screw extruder at 110° C. to produce masterbatch particles;

[0076] The plastic particles obtained in the above steps are extruded in a single screw extruder at 110°C to obtain a tubular semi-finished product with a wall thickness of 0.5-1.5 mm, and then a tubular finished casing with a wall thickness of 0.35-0.75 mm is obtained by electron accelerator or cobalt 60 irradiation cross-linking, vacuum or pressure expansion molding and other processes.

[0077] Example 3

[0078] First, this embodiment provides a low-odor formula: in parts by weight, the raw materials for its preparation include 48.3 parts of ethylene-vinyl acetate copolymer, 1.5 parts of a compatibilizer, 45 parts of a flame retardant, 0.2 parts of an antioxidant, and 5 parts of coffee grounds.

[0079] The brand of the ethylene-vinyl acetate copolymer is Mitsui Dupont V421, and the VA content is 28%-29%.

[0080] The compatibilizing agent is a commercially available maleic anhydride grafted EVA polymer, and the grafting rate is preferably 0.8-1%.

[0081] The flame retardant is a compound of aminosilane-modified ore-process magnesium hydroxide and coated red phosphorus in a weight ratio of 5:1;

[0082] The antioxidant is 1010.

[0083] The bio-based filler is a mixture of one or more ground and extracted coffee powders (powder particle size is 2-20 μm, or between 6000 mesh and 600 mesh).

[0084] Secondly, this embodiment provides a method for preparing a heat shrinkable sleeve, which at least includes the following steps:

[0085] Blending ethylene-vinyl acetate copolymer, a compatibilizing agent, a flame retardant, an antioxidant and a bio-based filler and extruding the mixture through a twin-screw extruder at 110° C. to produce a masterbatch pellet;

[0086] The plastic particles obtained in the above steps are extruded in a single screw extruder at 110°C to obtain a tubular semi-finished product with a wall thickness of 0.5-1.5 mm, and a tubular finished sleeve with a wall thickness of 0.35-0.75 mm is obtained through electron accelerator or cobalt 60 irradiation cross-linking, vacuum or pressure expansion molding and other processes.

[0087] Comparative Example 1

[0088] 1 part of coffee grounds described in this embodiment.

[0089] Comparative Example 2

[0090] In this embodiment, no coffee grounds are added, but 1 portion of plastic masking agent or flavoring agent is added.

[0091] Comparative Example 3

[0092] This embodiment coffee grounds 5 parts.

[0093] Performance Test 1

[0094] According to the standard ASTM D2671, the material mechanical properties of the samples obtained in Examples 1-3 and Comparative Examples 1-3 were tested, and the tensile strength>13MPa was recorded as A, the tensile strength was 11-12MPa was recorded as B, the tensile strength was 10-11MPa was recorded as C, and the tensile strength was <10MPa was recorded as D. The elongation at break>400% was recorded as A, the elongation at break 300%-400% was recorded as B, the elongation at break 200%-300% was recorded as C, and the elongation at break <200% was recorded as D. After aging at 158 ​​degrees for 168 hours, the mechanical properties of the materials were tested. Tensile strength > 10MPa was recorded as A, tensile strength 8-10MPa was recorded as B, tensile strength 5-7MPa was recorded as C, elongation at break > 280% was recorded as A, elongation at break 200%-280% was recorded as B, elongation at break 150%-200% was recorded as C, and elongation at break < 100% was recorded as D.

[0095] Performance Test 2

[0096] According to the standard UL94 HB horizontal combustion standard, the thickness of the sample is 3mm; the flame retardant properties of the samples obtained in Examples 1-3 and Comparative Examples 1-3 are tested. The self-extinguishing within 15S without igniting the absorbent cotton meets the V-0 requirement and is recorded as A, the burning time within 10-30s without igniting the absorbent cotton is recorded as B, and the burning time within 10-30s igniting the absorbent cotton is recorded as C.

[0097] Performance Test 3

[0098] Refer to national standard Q / LQB C-260-2016; test odor at 20 degrees, 40 degrees and 80 degrees respectively

[0099] variable Temperature ℃ Storage time How to operate 1 23±2 (24±1)h a, b, c, d, f 2 40±2 (24±1)h a, b, c, d, f 3 80±2 2h±10min a, c, e, f

[0100] a) For variables 1 and 2, add 50 ml of deionized water to the container (use a 1L or 3L container as appropriate). For variable 3, do not add water to the container;

[0101] b) Place the test sample on the stainless steel bracket inside the gas cylinder. If necessary, use wire mesh to fix it to avoid direct contact with water;

[0102] c) Close the container tightly and place it in an oven for preheating;

[0103] d) For variables 1 and 2, the odor was evaluated immediately upon removal of the container from the oven;

[0104] e) For variable 3, after being taken out of the oven, the container was placed in the air to cool to 60 ± 5 °C before the odor evaluation was conducted. After the evaluation by the three testers, the container was put back into the oven for 30 minutes at an oven temperature of 80 ± 2 °C, after which it was taken out again and the other testers conducted the identification evaluation;

[0105] f) For the evaluation of the container (normal), the number of evaluators shall be at least 5, and the difference between the scores given by each person shall not be greater than 1.5 points; if it is greater than 1.5 points, it is necessary to re-evaluate with 6 people. Generally speaking, 6 people are required to conduct a test.

[0106] Odor rating

[0107] grade Pricing Standards 1 No odor 2 There is an odor, but it is not disturbing 3 There is a noticeable smell, but no disturbing smell 4 Disturbing odor 5 Has a strong, disturbing odor 6 There is an unbearable smell

[0108] Performance Test 4

[0109] After being placed at room temperature for 6 months, Q / LQBC-260-2016 tested the odor at 20 degrees, 40 degrees and 80 degrees.

[0110] Performance Test Table

[0111]

[0112] From the above data, it can be seen that the heat shrinkable material provided by the embodiment of the present invention has good compatibility through the mutual mixing of the optimal proportion of bio-based fillers. The heat shrinkable sleeve made of the heat shrinkable material is placed for 3 to 6 months. During the process, there is no irritating odor at 20 degrees, 40 degrees, and 80 degrees. The manufacturing process is simple, convenient, environmentally friendly, and has a low manufacturing cost.

[0113] In the technical solution provided in this embodiment, bio-based coffee filter residues are added to the radiation-modified polymer. Due to the porous structure of the coffee filter residues, they can be effectively connected to the polymer molecular chain under the action of the radiation. At the same time, without changing the basic properties of the original polymer, the irritating odor caused by the degradation of the polymer caused by high-energy radiation and the unfriendly odor of the raw material itself can be effectively improved. At the same time, the addition of the bio-based coffee filter residues accelerates the aging and degradation of the material, which is more beneficial to the environment.

[0114] The above are only some embodiments of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A heat shrinkable material, characterized in that: By weight, it includes the following components:

2. The heat shrinkable material according to claim 1, characterized in that: The melt index of the ethylene-vinyl acetate copolymer is 1.5-5 grams per minute (g / min), and the content of vinyl acetate (VA) is 13%-30%.

3. The heat shrinkable material according to claim 1, characterized in that: The compatibilizing agent is a maleic anhydride graft copolymer, wherein the content of maleic anhydride comonomer is 0.8-1%wt (weight content percentage).

4. The heat shrinkable material according to claim 1, characterized in that: The flame retardant is compounded from aminosilane-modified ore-process magnesium hydroxide and coated red phosphorus, wherein the weight ratio of the aminosilane-modified ore-process magnesium hydroxide to the coated red phosphorus is 5:

1.

5. The heat shrinkable material according to claim 1, characterized in that: The antioxidant is a combination of one or more of amines, heterocycles, phenols, thioesters and phosphites.

6. The heat shrinkable material according to claim 1, characterized in that: The bio-based filler is coffee powder.

7. The heat shrinkable material according to claim 6, characterized in that: The preparation method of the coffee powder comprises: Grinding coffee beans to extract coffee powder, wherein the coffee powder has a particle size of 2-20 microns (μm), or between 6000 mesh and 600 mesh; The coffee powder is dried.

8. A heat shrinkable sleeve, characterized in that: include: The heat shrinkable material according to any one of claims 1 to 7 is used, wherein the heat shrinkable material comprises the following components in parts by weight:

9. A method for manufacturing a heat shrinkable tube, characterized in that: include: Take the heat shrinkable material as described in any one of claims 1 to 7; Extruding and granulating the heat shrinkable material at a preset temperature to obtain masterbatch particles; The masterbatch particles are extruded and formed, and a heat shrinkable sleeve is prepared by radiation cross-linking and expansion forming.